Potential of Bioactive Compounds in Hepatotoxicity Using Primary Cell Culture Method: A Systematic Review - Illahi, Angga Illahi Kurnia; Raihan, Afdhal; Petrovsky, Ivan; Maliza, Rita (Universitas Muhammadiyah Surakarta, 2024)
Hepatotoxicity is a condition characterized by liver cell damage caused by toxic chemicals. This article aims to explore the effects of compounds that contribute to mitigating hepatotoxicity, focusing on in vitro studies, particularly primary cell culture. In this systematic review, we conducted searches in the PubMed, Science Direct, and Google Scholar databases to find articles published between 2008 and 2022. Several active compounds were identified, including N-Benzylpiperazine (BZP), 1-(3-trifluoromethylphenyl) piperazine (TFMPP), antimycin A, coenzyme Q (CoQ) substrates, the antioxidant Vitamin C, L-glutamine (Gln), Nimesulide, Luteolin, glutathione, angelica sinensis polysaccharide (ASP) from Angelica sinensis, ammonium glycyrrhizin (CAG) from Glycyrrhiza glabra, L-arginine, silymarin from Silybum marianum, and glucurolactone (GA). However, only six compounds were shown to have remedial and treatment effects on hepatotoxicity and utilized primary cell culture with MTT Assay. These six compounds are Luteolin, Glutathione (GSH), Angelica sinensis polysaccharide (ASP) from Angelica sinensis, Ammonium glycyrrhizin (CAG) from Glycyrrhiza glabra, Antimycin A (AA), and Glutamine (Gln). The mechanism of action of these compounds involves preventing further damage to liver cells and repairing cells that have already been damaged. In summary, these compounds play a significant role in addressing hepatotoxicity caused by toxic substances and drugs.